TechConnect Industry Landscape Report 2025: Building Human-Tech Skill Complementarity - Fu, Na; Li, Jiamin (My University, 2025)
This Industry Landscape Report Year 1 (D1.2), produced as part of Work Package 1 in the TechConnect project, presents a comprehensive overview of how advanced digital technologies (ADTs) are shaping the nature of work, workforce capabilities, and skill development across sectors. Rooted in the concept of Human–Tech Skill Complementarity, the report highlights the evolving relationship between human and digital skills and the organisational challenges arising from this transformation. The findings draw on both quantitative and qualitative analysis of the results from an industry survey, participated by both employees and managers. All workers shared their firsthand experiences of using digital technologies at work. Managers additionally reported on workforce digitalisation and upskilling efforts. To ensure broader relevance, the analysis includes a comparison between EU and non-EU respondents, across both employee and managerial perspectives. Additionally, insights are benchmarked against key European studies and policy frameworks to contextualise the findings within the broader digital transformation landscape. Key findings include: • The widespread use of ADTs across roles, sectors, and regions. Technologies are applied in diverse and expanding ways, from task automation to decision support and collaboration enhancement. • The growing recognition of complementarity between human and digital skills. Rather than replacing human input, ADTs are creating new demands for human skills such as problem-solving, creativity and interpersonal skills, reinforcing the need for integrated skill strategies. • Organisations are encountering significant challenges in managing this shift. Challenges include aligning digital investments with workforce readiness, addressing uneven access to training, and adapting leadership and HR practices to a more digital-ready workplace. The report concludes with practical recommendations for business leaders, HR professionals, employees, education and training providers, and policymakers. These focus on advancing workforce strategies that integrate human and digital skill development, fostering cross-functional collaboration, strengthening data use and evaluation practices, and promoting inclusive, future-oriented learning ecosystems. Serving as the empirical foundation of the TechConnect project, this report underpins the practical activities in Work Package 2 (Observational Case Studies) and Work Package 3 (Interventional Pilot Studies). It functions as a diagnostic tool, offering a snapshot of current practices and challenges. In addition, it is a strategic resource to guide organisational decision-making, shape policy interventions, and inform the design of responsive, high-impact education and workforce development initiatives for the accelerated and inclusive digital transformation.
SUBMITTED
Keywords: Creative Technologies; Digital Engagement; Digital Humanities; Inclusive Society; International Integration; Advanced digital technologies; Digital Skills; Human skills; Human-Tech Skill Complementarity; Industry analysis